2019
DOI: 10.9734/arrb/2019/v32i430089
|View full text |Cite
|
Sign up to set email alerts
|

Dried Pig Feces: Impacts on Growth, Haematology and Histology of Clarias gariepinus

Abstract: Aims: Improper utilization and disposal of pig faeces in pig farms have been a great concern due to their hazards and risks they constitute to the environment. This situation calls for effective utilization of pig Feces for fish feed. This project was designed to provide information on safe level of Dried Pig Feces (DPF) on growth, histology and haematology of Clarias gariepinus. Study Design: A twelve week feeding trial experiment was conducted using one hundred and fifty samples of C. gariepinus juveniles. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Turner et al (2002) reported phytic acids to have a negative effect on amino acid digestibility, thereby causing problems to non-ruminant animals due to insufficient phytase needed for hydrolysis of phytic acids. Similarly, Ajiboye et al (2017) and Ajiboye et al (2019) reported poor growth performance in C. gariepinus as the level of dried poultry droppings and dried pig feces increased in the diets of the fish. The authors attributed poor growth performance recorded at 100% level of inclusion to the high level of microbes and phytochemicals in the formulated diets.…”
Section: Discussionmentioning
confidence: 94%
“…Turner et al (2002) reported phytic acids to have a negative effect on amino acid digestibility, thereby causing problems to non-ruminant animals due to insufficient phytase needed for hydrolysis of phytic acids. Similarly, Ajiboye et al (2017) and Ajiboye et al (2019) reported poor growth performance in C. gariepinus as the level of dried poultry droppings and dried pig feces increased in the diets of the fish. The authors attributed poor growth performance recorded at 100% level of inclusion to the high level of microbes and phytochemicals in the formulated diets.…”
Section: Discussionmentioning
confidence: 94%